Identifikasi dan Pengelolaan Risiko Lokasi Proyek di Wilayah Bali: Pendekatan Kualitatif Melalui Wawancara Mendalam dengan Para Manajer Proyek - M. Alit Suryawan (Universitas Batanghari Jambi, 2026)
This study aims to explore the identification and management of location-based risks in construction projects in Bali through a qualitative approach using in-depth interviews with ten experienced project managers. As an internationally recognized tourism destination, Bali possesses complex and multidimensional risk characteristics encompassing physical-geographical, socio-cultural-customary, and regulatory-permitting aspects. The research employed a phenomenological study design to understand the practical experiences of project managers in dealing with location-related risks directly in the field. The findings reveal three primary clusters of location risks consistently encountered by project managers, namely physical-geographical risks, socio-cultural-customary risks, and regulatory and permitting risks. Socio-cultural risks rooted in local customary systems such as desa pakraman, awig-awig, and the Tri Hita Karana concept emerged as the main distinguishing factors compared to other regions in Indonesia, as they directly affect project schedules, costs, and design processes. In addition, dynamic regulations and Bali’s disaster-prone geographical conditions further increase the complexity of construction project management. The risk management strategies implemented by project managers are adaptive and contextual, emphasizing the involvement of customary communities from the pre-construction stage, periodic updates of the risk register, and the application of combined avoidance, mitigation, and acceptance strategies based on the characteristics of each risk. This study contributes to the development of a locality-based risk management framework relevant to construction projects in tourism areas across Indonesia while highlighting the importance of integrating local cultural aspects into modern risk management practices.